Task Based Test Case Generation on Available Gestural Interaction of Smartphone for Improved Safety and Ergonomics in Real Driving Scenario - Ganasan, J. (International Association of Online Engineering, 2022)
Mobile phones that accept input by a userâs finger motion are becoming increasingly common. However, they still have challenging problems to research, such as the ergonomic and safety aspects. As an outcome, more research required its capabilities and a critical examination of the existing gestural interfaces and how they assist driversâ activities while driving. This research paper attempts to present a comprehensive understanding of possible gestures on smartphones by conducting user testing with sample data of 30 drivers from three different age groups. The user testing was performed in an actual driving environment. Observation and interviews were carried out to study driversâ behavior while driving. The data gathered were then interpreted into action and motivation levels. The action level was defined by how drivers interact with smartphones while driving, and in motivation level, a study on why drivers interact in that manner was conducted. The results were then drawn to a table with the task carried out during user testing. In conclusion, this research aims to consider all these driversâ issues while driving. This is to determine how a more advanced gestural interaction of smartphone interfaces may be created to meet driversâ safety and ergonomic concerns Â© 2022. International Journal of Interactive Mobile Technologies.All Rights Reserved.